A anterioridade dos processos emocionais na estruturação do juízo moral - Teles, Johnny Clayton Cardoso (2020)
From the Greeks to the Romans, from Judeo-Christian culture, emotions were either underestimated or relegated to mere impulses, appetites and desires. Although Hume has emphasized the influence and sometimes the dominance of emotions over reason, or even a rationalist as Kant, has observed that moral judgments have been accompanied by moral sentiments, only in recent decades, with the revolution and maturation of the cognitive sciences, researches in evolutionary psychology and the study of primates, affective revolution, and finally brain mapping and the development of neuroscience, have led to a deepening of the relationship between morality and emotions. The research outlined here aims, briefly, to defend the thesis, based on four cognitive models, that emotions, to a greater or lesser extent, to a greater or lesser intensity, have an earlier dominant role in structuring moral judgment and, consequently, in making decisions, whether moral or not. The first model is that of A. Damásio, who demonstrates that emotions play a central role in social cognition and decision making. Concepts and definitions about emotion and feelings should be approached in order to understand the model, or the somatic marker hypothesis. The central idea is that such processes depend significantly on the neural substrates that regulate homeostasis, emotions, and feelings, a process influenced by markers. The second model is that of J. Greene's intituled Dual Process Theory. Greene's cognitive model tends to perceive emotions as either automatic processes or manual processes that tell us what to do, but which also tends between individual and collective interests, that is, tribalists. Overall, Greene's research follows and supports the claim that reason is not sufficient cause for judgment or moral behavior - emotion lies in structure. J. Panksepp's Affective Neuroscience, grounded in evolutionary studies and animal research, aims to reconfigure the role of basic emotions through the theory of emotional or affective circuits (systems), argues that the emotional process, including feelings, plays a causal role in the chain of events that control the actions of both humans and animals. Finally, J. Haidt reevaluates the roles of reflection and reasoning in moral judgment which is predominantly intuitive and driven mainly by automatic emotional responses that are effortless and produced by unconscious processes, i.e moral judgment is caused by moral intuitions, fast and is followed (when necessary) by slow thinking and ex post facto. We try to confirm that more and more evidence and research in cognitive psychology and neuroscience suggests that moral judgment is more a matter of emotion and affective intuition than deliberate reasoning, that is, in practice, affective reactions are so fast and impulsive that they work as visors on horses.